Respuesta :

[tex]\frac{15a^2\left(a-1\right)}{8\left(2a+3\right)}\cdot \frac{10\left(2a+3\right)}{3a}[/tex]

[tex]\mathrm{Apply\:the\:fraction\:rule}:[/tex]

[tex]\frac{a}{b}\cdot \frac{c}{d}=\frac{a\:\cdot \:c}{b\:\cdot \:d}[/tex]

[tex]=\frac{15a^2\left(a-1\right)\cdot \:10\left(2a+3\right)}{8\left(2a+3\right)\cdot \:3a}[/tex]

[tex]\mathrm{Cancel\:the\:common\:factor:}\:2a+3[/tex]

[tex]=\frac{15a^2\left(a-1\right)\cdot \:10}{8\cdot \:3a}[/tex]

[tex]\mathrm{Factor\:the\:number:\:}\:15=3\cdot \:5[/tex]

[tex]=\frac{3\cdot \:5a^2\left(a-1\right)\cdot \:10}{8\cdot \:3a}[/tex]

[tex]\mathrm{Cancel\:the\:common\:factor:}\:3[/tex]

[tex]=\frac{5a^2\left(a-1\right)\cdot \:10}{8a}[/tex]

[tex]\mathrm{Factor\:the\:number:\:}\:10=2\cdot \:5[/tex]

[tex]=\frac{5a^2\left(a-1\right)\cdot \:2\cdot \:5}{2\cdot \:4a}[/tex]

[tex]\mathrm{Factor\:the\:number:\:}\:8=2\cdot \:4[/tex]

[tex]=\frac{5a^2\left(a-1\right)\cdot \:2\cdot \:5}{2\cdot \:4a}[/tex]

[tex]\mathrm{Cancel\:the\:common\:factor:}\:2[/tex]

[tex]=\frac{5aa\left(a-1\right)\cdot \:5}{4a}[/tex]

[tex]\mathrm{Apply\:exponent\:rule}:[/tex]

[tex]a^{b+c}=a^b\cdot \:a^c[/tex]

[tex]a^2=aa[/tex]

[tex]\mathrm{Cancel\:the\:common\:factor:}\:a[/tex]

[tex]=\frac{5a\left(a-1\right)\cdot \:5}{4}[/tex]

[tex]\mathrm{Multiply\:the\:numbers:}\:5\cdot \:5=25[/tex]

[tex]=\frac{25a\left(a-1\right)}{4}[/tex]

[tex]\mathrm{I\:hope\:that\:I\:helped\:you\:!}[/tex]